Teaching English through sports: A case study - Christopher, Anne Althea; Dzakiria, Hisham; Mohamed, Abdul Halim (Asian EFL Journal Press, 2012)
Teaching English as a Second Language through sports activities gives immense benefits to learners.It promotes active learning of the language in any environment, whether urban or rural. It not only enhances learning of the English Language but also the intellectual, physical and social development of the learners. The method of teaching English through sports activities was carried out on one class of undergraduates, consisting of 15 learners.In the classroom, learners were first introduced to some general information or to the history of a particular sport like badminton or basketball. Discussions in small groups were conducted of the particular sport they would be participating in outdoors or at the sports complex in the following lesson.By the end of the class, they had become familiar with the vocabulary related to the sporting activity concerned.In the follow-up lesson, they began their sporting activity. Observations were made by the instructor to ensure the learners used only English throughout their activity when interacting with the people around them.After the physical activity, learners were asked to describe their feelings, their surroundings, the rules and regulations of the sport, their performances, and the skills and actions involved. Learners were found to be more expressive in using the English Language after the sports activity.They were more confident and motivated than when they were in the classroom. There was also better social interaction and a sense of sharing among their classmates, not to mention an improvement in their use of the English Language.